Лингвоаксиологический взгляд на типы речевых актов (на материале устной разговорной речи) - Пикулева, Юлия (Studia Rossica Posnaniensia, 2019)
The report is devoted to the linguoaxiological description of types of speech acts. The author comes to the conclusion that direct and indirect linguistic signals of verbali- zation of perceptions of values and attitudes can be allocated among the types of speech acts. Such speech acts as representatives, commissives, directives, declaratives can transfer value meanings with varying degrees of certainty. The materials are a corpus of conversations of citizens of the Urals – vernacular speakers. It is possible to identify some of the core national and regional values based on the analysis of the material.